Phaeoacremonium cinereum: an uncommon microorganism causing rare occurence of isolated right sphenoid fungal rhinosinusitis - Wong, Chyau Hong; Chew, Shiun Chuen (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Fungal rhinosinusitis (FRS) can be either invasive or non-invasive, with the later characterized by the disease confined to the paranasal sinuses, mucous membrane, and bone wall without fungal invasion, including fungus ball (FB) and allergic fungal rhinosinusitis. Infection involving sphenoid sinus usually provokes headache or involvement of the surrounding cranial nerves due to its unique and posterior location in the nasal cavity. We encountered a case of right isolated sphenoid non-invasive fungal sinusitis caused by rare microorganism namely Phaeoacremonium cinereum. The disease was diagnosed based on clinical, endoscopy, radiological findings as well as specimen culture and sensitivity. Computed tomography (CT) scan provides information regarding the extension of sinusitis to dental, orbit, cranial bones and intracranial region. Once the diagnosis of sphenoid fungal rhinosinusitis is made, endoscopic sphenodotomy is the treatment of choice.